PENYULUHAN DAN BIMBINGAN AKUNTANSI PRAKTIS PADA UMKM USAHA DAGANG DI SUKARAMAI TRADE CENTER PEKANBARU RIAU - Rona Naula Oktaviani; Devi Kurniawati; Firdaus AR; Aswin Putra (UIR Press, 2024)
This Community Service (PKM) was carried out at the Sukaramai Trade Center (STC) Pekanbaru Riau. Limited knowledge of MSMEs in terms of keeping financial records or bookkeeping. So, the aim of this PKM is to provide knowledge and improve the abilities of MSMEs at STC in recording and managing the finances of their trading businesses. The method used is that the PKM team visits MSMEs directly to their respective shops with (socialization, discussions, and providing pocket books). The conclusion of this service shows that PKM activities have been successfully implemented and achieved significant results, as published in the Riau Pos.co Online Mass Media and have had a positive impact on MSMEs at STC and opened up opportunities for further service activities in the future.